ENCOURAGING THE PROTECTION OF INTELLECTUAL PROPERTY RIGHTS TO "OIL MANDAR" IN THE GEOGRAPHICAL INDICATIONS REGIM - Paserangi, Hasbir (Awang Long Law Review, 2018)
Oil mandar or "lomoq mandar" is one of the processed products of coconut that has a fragrant and distinctive aroma. In addition to the distinctive aroma, this oil also has a longlasting resistance that can be stored for more than a year, even without the use of synthetic chemical preservatives. Although this oil is traditionally processed, but this oil is not less competitive with the production of palm oil manufacturers. On the Polewali-Majene axis road we will find a cluster of palm trees waving palm, a familiar scene in the eyes of locals who are the main producers of coconut cooking oil. The geographical and socio-cultural conditions that support make this plant very strategic to be developed. So naturally if this area is held as a coconut producing center in West Sulawesi. Polewali Mandar area as an area that has huge natural resources, one of them is coconut fruit with "Mandar Oil" product, of course have big importance to this problem especially in strengthening people economy so that local government must take an active role to realize legal protection effort in the Geographical Indication regime as stipulated in Government Regulation no. 51 of 2007 About Geographical Indications. The diversity of natural resources in Polewali Mandar is a great God's gift to the Mandar people, most of whom are Mandar Craftsmen other than Fishermen, Silk Woven craftsmen, and Chocolate producers (cocoa). The existing condition has the potential to gain enormous economic benefits when developed and managed commercial and planned. Protecting the potential of existing resources can also increase the source of community income. The form of effort that can be done by local government with Mandar society in protecting Mandar Oil product is by applying Intellectual Property Right registration in Geographical Indication regime to Directorate General of Intellectual Property Rights in Jakarta.